Review of physiotherapeutic methods used in patients with osteoporosis - Chłystek, Joanna; Pietsch, Julia; Golus, Anna; Abramczyk, Agata; Łakomski, Mateusz (Journal of Education, Health and Sport, 2018)
This article is a review of current literature about physiotherapeutic methods used in osteoporosis including physical activity and physical therapy. Osteoporosis is a systemic disease classified as a civilization disease, which is significantly associated with gender, age, low body weight, and lifestyle. Most often it concerns older adults and is also characteristic for postmenopausal women. The research presented in this article suggests the positive influence of physiotherapy (i.e. aerobic exercises and resistance training and also physical therapy) on osteogenic processes, bone mineral density, pain and decrease the risk of falls.